Myoclonus - R. Rimšienė; S. Andruškevičius; R. Mameniškienė (Neurologijos seminarai)
Myoclonus is a sudden, short, involuntary single or recurrent twitching of a muscle. Myoclonus is classified according to the etiology and physiological mechanism of development. They can be physiological and pathological, inherited or acquired due to various structural brain damage or systemic diseases. The article presents etiologies and classification of myoclonus. The most common diseases, syndromes, and structural changes of the brain that can cause myoclonus are reviewed. Myoclonus examination and treatment aspects are also discussed in the article.